139k views
2 votes
Rule 1: Multiply x by 5 to get y.
Rule 2: Add 12 to x to get y.

User Jeeeyul
by
5.5k points

2 Answers

6 votes

Answer: B) (3,15)

finale answer is 3,15

User Lawand
by
5.8k points
2 votes

Answer:B) (3,15)

Step-by-step explanation:

Let's try rule 1.

x × 5 = y

5x = y -> 1

Now let's try rule 2.

12 + x = y

12+ x = y -> 2

Equating eqn. 1 and 2,

5x = 12 + x

4x = 12

x = 3

From eqn. 1,

5x = y

5 × 3 = y

Hence, y =15

So the final answer is B) (3,15).

User Ruben Trancoso
by
5.2k points